Post-tenure faculty review and renewal III : - Licata, Christine M. (Anker Pub. Co., 2006)
A joint publication from the American Association for Higher Education’s New Pathways Project and Anker Publishing Company, this is the final book in a series on review, renewal, and vitality of tenured faculty. This volume brings together the findings from nine different institutional case studies, focusing on the effectiveness and outcomes of post-tenure review. Providing the most comprehensive report on the outcomes of post-tenure review within senior-level institutions as reported by campus faculty and administrators, this is the only national study to date that uses multiple methods of data collection to understand how campuses of differing size, mission, and culture experience the review process and describe its impact.